Sensing the electrical activity of single ion channels with top-down silicon nanoribbons. Issue 2 (12th June 2018) - Zhou, Weiwei; Mu, Luye; Li, Jinfeng; Reed, Mark; Burke, Peter J
Abstract: Using top-down fabricated silicon nanoribbons, we measure the opening and closing of ion channels alamethicin and gramicidin A. A capacitive model of the system is proposed to demonstrate that the geometric capacitance of the nanoribbon is charged by ion channel currents. The integration of top-down nanoribbons with electrophysiology holds promise for integration of electrically active living systems with artificial electronics.